(untitled) (Revista Brasileira Multidisciplinar, 2021)
Objective: To establish a baseline of knowledge regarding about inappropriate therapy, virulence and resistance in a cohort of patients infected with S. aureus. Methods: Retrospective cohort study in tertiary-care university hospital was employed to evaluate the risk factors and the impact of inappropriate therapy among patients with Staphylococcus aureus infections, resistance and virulence. To assess the presence of the genes was performed PCR. Results: Patients with MRSA were older and hospitalized 17 days longer than those with MSSA infection, which were in ICU with a bloodstream infection. 50.0% received inadequate antibiotic therapy and we found virulence factors associated with MRSA (mecA, LukS, fnbB and clfA genes). Conclusion: These data show that surveillance studies related to Staphylococcus aureus infections remain essential to identify resistance and inform policy on resistance.